Thermal tomography characterization and pulse-phase thermography of impact damage in CFRP, or why end users are still reluctant about practical use of transient IR thermography; Thermosense XX, Orlando, April 13, 1998 - Vavilov V. P. Vladimir Platonovich; Marinetti S. Sergio; Grinzato E. Ermanno; Bison P. Paolo (1998, 1998)
Title screen